Comparative Analysis of Tensile Strength of Steel Tubing Pipe Welding Results Using SMAW and MIG Welding with 140A Current - Tri Aulia, Yuni; Ariyon, Muhammad; Fitriani, Fitriani; Sebayang, Alexander; Tarigan, Efrata (Malikussaleh University, Aceh, Indonesia, 2025)
Welding is a crucial technology in modern manufacturing processes, widely applied in automotive, oil refineries, and other industries. This study focuses on two standard welding techniques: Gas Metal Arc Welding (GMAW) and Shielded Metal Arc Welding (SMAW). GMAW uses argon gas as a shielding gas, and the ER70S-6 electrode has a 1.0 mm diameter, while SMAW employs the E7018 electrode with a 2.6 mm diameter. Both methods are tested on ASTM 106 Grade B steel, a commonly used material in various industries. The primary goal of this research is to evaluate the tensile strength of steel specimens welded using MIG and SMAW. The tensile strength of raw material, as well as the welded materials, is measured to assess the quality of the welds. The results show that the tensile strength of the raw material is 648.26 kgf/mm². After welding, the tensile strength for the MIG-welded material is 540.79 kgf/mm², while the SMAW-welded material achieves a higher tensile strength of 616.17 kgf/mm². These values highlight the significant difference in performance between the two welding techniques. SMAW welding provides the best joint quality among the two methods, with a tensile strength value of 616.17 kgf/mm². This study underscores the importance of selecting the appropriate welding technique based on the desired strength and application, with SMAW proving superior for this particular material. These findings contribute valuable insights into material technology and welding, offering a reference for future industrial applications.